Somatostatin inhibits multireceptor stimulation of cyclic AMP formation and corticotropin secretion in mouse pituitary tumor cells. - Heisler, S (1982)
The AtT-20/D16-16 mouse pituitary tumor cell secretes corticotropin (ACTH) in response to corticotropin-releasing factor (CRF), (-)-isoproterenol, and vasoactive intestinal peptide (VIP). These responses are associated with a rapid increase in cyclic AMP formation. Somatostatin (SRIF) markedly decreases the stimulatory effect of CRF, (-)-isoproterenol, and VIP on both cyclic AMP formation and immunoreactive ACTH secretion. Forskolin and cholera toxin, adenylate cyclase activators, also stimulate cyclic AMP formation and ACTH secretion in AtT-20 cells and these responses are all inhibited by SRIF. The ACTH secretory responses to melittin and to the calcium ionophore A23187, neither of which increases cyclic AMP in AtT-20 cells, were not inhibited by SRIF. SRIF did not affect the binding of a tritiated beta-adrenergic receptor antagonist to AtT-20 membranes nor did it decrease basal cyclic AMP formation even in the presence of excess phosphodiesterase inhibitor, indicating that the reduction of cyclic AMP levels by SRIF did not involve either an interference with beta-adrenergic agonist binding to receptors or stimulation of cyclic AMP degradation. These results indicate that the inhibition of CRF-, (-)-isoproterenol-, and VIP-stimulated ACTH secretion by SRIF may be regulated by its inhibitory action on adenylate cyclase.